Pengaruh Penggunaan Media Visual Terhadap Prestasi Belajar Materi Penyakit Menular dan Tidak Menular Siswa Kelas V di SD Negeri Bantul Timur - Sari, Kartika; Subarno, Subarno; Sujati, Heronemus (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
This study aims to examine the influence of visual media on the learning outcomes of communicable and non-communicable diseases among fifth-grade students at SD Negeri Bantul Timur, Bantul Regency. This research uses a One-Group Pretest-Posttest design with a survey method and a test approach. The subjects of the study include half of the fifth-grade students at SD Negeri Bantul Timur, totaling 35 respondents. Data collection was conducted through a survey using test instruments. Data analysis was carried out using a t-test, after first meeting the prerequisites of normality and homogeneity tests. The t-test results showed that the calculated t value (t hitung) = -5.729 and the t table value (t tabel) (13)(0.05) is 1.697. Since the calculated t value is greater than the t table value (t hitung > t tabel), it is concluded that there is a significant influence of the use of visual media on the learning outcomes of communicable and non-communicable diseases. The average pretest score was 65.86, while the posttest score was 77.14. The average score increased by 11.28 or 17.13%, leading to the conclusion that visual media is effective in improving the learning outcomes of communicable and non-communicable diseases among fifth-grade students at SD Negeri Bantul Timur, Bantul Regency.